Nadmierne korzystanie z sieci społecznościowych przez młodzieŜ szkolną – charakterystyka zjawiska - Jarczyńska, Jolanta (Studia Edukacyjne, 2020)
Social networking sites (SNS), popularly called portals, are sites that combine multiple functions. Users might communicate by SNS with their friends, share photos and movies or participate in groups. SNS satisfy their users’ needs such as the need to connect or to self-present. These functions of SNS make them attractive. It is not surprising, therefore, that in recent years there has been an increasing number of people, especially young ones, using social networking sites. Facebook (FB)is the most popular social network in the world. Statistics carried out by FB indicate a rapid increase in the number of Internet users who make use of this particular social networking site. The article presents the characteristics of the phenomenon of school students’ excessive use of social networking sites. It defines the basic concepts, describes the diagnostic criteria for abuse of social networking sites and theories to explain this behavior. It shows the loss and benefits of excessive use of social networks and presents tools used in research to measure school students’ excessive use of social networking sites.